Devising an approach to the construction of an adapted model of the reconnaissance-fire system functioning - Maistrenko, Oleksandr; Saveliev, Andrii; Pechorin, Oleksandr; Karavanov, Oleksandr; Stetsiv, Stanislav; Shvets, Mykola; Lykholot, Oleksandr; Voitenko, Serhii; Khimchenko, Oleksandr; Kondratenko, Yulii (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the operational model of a reconnaissance-fire system. The problem that was solved is the lack of an approach to building a model of the functioning of a combat system, in particular a reconnaissance-fire system, which would take into account the influence of all subsystems and include the necessary number of system states. An improved procedure for building an adapted operational model of the reconnaissance-fire system has been proposed. The essence of the improved methodology is the formalization of processes through the definition of system states and intensities of transitions from state to state. The improved procedure is based on the Kolmogorov-Chapman equations and the goal tree construction method. A feature of the improved methodology is the breakdown of the states of the reconnaissance-fire system by hierarchy levels, which allows taking into account more necessary states of the system. The field of practical use of the improved methodology is planning and management processes during the development of action algorithms during combat operations. An adapted operational model of the reconnaissance-fire system has been built. The essence of the model is to determine the probability of the reconnaissance-fire system being in a certain state based on the Chapman-Kolmogorov equations, taking into account the necessary level of detail in the process of its operation. Special feature of the proposed model is that it makes it possible to model by taking into account 39 states of the system with the necessary accuracy both for the system as a whole and separately for subsystems. This is explained by the fact that the test of the adequacy of the model showed that the discrepancy of the results is within the statistical error from 2 to 9 %. The field of application of the adapted operational model of the reconnaissance-fire system is the processes of making a decision on the application of the operation of the intelligence-fire system during hostilities and their management during combat operations.